(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to shed light on an important topic, namely the indicators of monetary stability and their impact on achieving financial inclusion, as monetary stability is one of the priorities of monetary and financial policy in Iraq, because of its great role in improving the performance of the financial and banking sector in Iraq, and the central bank has sought to provide financial services to large segments of Iraqi society, especially the segments deprived of these vital services, and the study has started from a main problem that is (do monetary stability indicators have an impact on achieving financial inclusion?) Which included a set of sub-questions to give an integrated scientific vision showing the effectiveness of monetary stability indicators in achieving Financial inclusion . The data of the indicators of monetary stability and financial inclusion in Iraq were analyzed and the impact between the independent and dependent variables was determined based on the descriptive analytical approach, which was prepared according to the data of the Annual Statistical Bulletin of the central bank for different years (2017-2022), where the research aimed to show the course of monetary stability indicators during the research period and their impact in achieving financial inclusion in Iraq. Using the statistical program (Eviews ) As a result, wider financial inclusion can be achieved by educating individuals about the importance of financial services and how to access them, as well as expanding the network of bank branches and improving the access of financial services to rural areas and remote communities .